2022
DOI: 10.1371/journal.pone.0279062
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of three online-related addictive behavior instruments among Bangladeshi school-going adolescents

Abstract: Background Due to the ease of access to the internet in modern society users have become more prone to experiencing addictive behaviors online. The present study aimed to develop and investigate the psychometric properties of the Bangla Internet Gaming Disorder Scale–Short-Form (IGDS9-SF), Gaming Disorder Test (GDT), and Bergen Social Media Addiction Scale (BSMAS) due to a lack of existing sound psychometric tools in Bangladesh. Methods A cross-sectional paper-and-pencil survey was carried out among 428 scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 90 publications
2
7
0
Order By: Relevance
“…The psychometric properties of the Malay version of the GDT demonstrated satisfactory level of internal consistency reliability in the present study, which was comparable to previous findings (Chiorri et al, 2023; Cudo et al, 2022b; Islam et al, 2022; Maldonado-Murciano et al, 2021). In concurrence with the existing literature (Islam et al, 2022; Wang & Cheng, 2020), the GDT score was found to be significantly correlated with the IGDS9-SF, BSMAS, time spent on social media, and time spent on gaming, supporting concurrent validity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The psychometric properties of the Malay version of the GDT demonstrated satisfactory level of internal consistency reliability in the present study, which was comparable to previous findings (Chiorri et al, 2023; Cudo et al, 2022b; Islam et al, 2022; Maldonado-Murciano et al, 2021). In concurrence with the existing literature (Islam et al, 2022; Wang & Cheng, 2020), the GDT score was found to be significantly correlated with the IGDS9-SF, BSMAS, time spent on social media, and time spent on gaming, supporting concurrent validity.…”
Section: Discussionsupporting
confidence: 91%
“…The psychometric properties of the Malay version of the GDT demonstrated satisfactory level of internal consistency reliability in the present study, which was comparable to previous findings (Chiorri et al, 2023; Cudo et al, 2022b; Islam et al, 2022; Maldonado-Murciano et al, 2021). In concurrence with the existing literature (Islam et al, 2022; Wang & Cheng, 2020), the GDT score was found to be significantly correlated with the IGDS9-SF, BSMAS, time spent on social media, and time spent on gaming, supporting concurrent validity. These results are consistent with previous studies on the relationship between GD and time spent on gaming (e.g., Cudo et al, 2020; Evren et al, 2020; Li et al, 2021; Pontes et al, 2021) and time spent on social media (Wong et al, 2020), indicating that increased severity of GD symptoms may be related to longer time spent on gaming and social media.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous research e.g., 28 , 29 , answering all four items with 4 ‘ Often ’ or 5 ‘ Very often ’ was operationalized as being indicative of disordered gaming. A study by Karhulahti and colleagues reported that the GDT had the highest levels of content validity compared to similar measures 30 while a recent study reported that the GDT showed adequate levels of criterion validity and convergent validity 31 . In the present study, the GDT exhibited adequate levels of reliability (α = 0.74; ω = 0.74; Composite Reliability [CR] = 0.74).…”
Section: Methodsmentioning
confidence: 99%
“…Cudo et al [13] reported a single-factor structure for the Polish version of the GDT. Islam et al [21] presented a unidimensional factor structure for the Bangla GDT (after correlating the error variances of GDT items 2 and 3). Chiorri et al [22] reported a single-factor structure for the Italian version of the GDT in the supplementary materials of their paper.…”
Section: Introductionmentioning
confidence: 99%